Penerapan Algoritma Fuzzy Logic Pada Sistem Pengukur Suhu Tubuh Manusia dan Hand Sanitizer Berbasis Arduino Uno R3 dengan Menggunakan Sensor Proximity - Putri Nova Sari; Mhd Zulfansyuri Siambaton; Tasliyah Haramaini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Maintaining health is very important for life, especially during the current Covid-19 pandemic. One of the protocols imposed by the government for people who are active in public spaces or open facilities is to check body temperature and hand sanitizer. In this research, a design for measuring body temperature and automatic hand sanitizer based on Arduino Uno is made which has a reminder alarm if the body temperature is NORMAL if the temperature is 35.8°C – 37.5°C and NOT NORMAL if the temperature is above 37.5°C. Where this tool will work after the hand is brought near to measure the temperature and at the same time issue hand sanitizer using the proximity sensor. Body temperature data is also displayed on the 16x2 (cm) LCD on the device. For data collection techniques, this research was carried out by means of observation and literature in accordance with the problems being studied.